2019
DOI: 10.1021/acsami.9b07942
|View full text |Cite
|
Sign up to set email alerts
|

Endowing the Lithium Metal Surface with Self-Healing Property via an in Situ Gas–Solid Reaction for High-Performance Lithium Metal Batteries

Abstract: The property of the solid electrolyte interphase (SEI) layer is of prime importance for the performance of lithium metal anodes. Replacing the spontaneously formed inhomogeneous and unstable SEI layer with a high-performance artificial SEI is an effective strategy. Herein, a self-healing SEI layer with high lithium-ion conductivity and a stable framework to address the issues of poor performance of lithium metal anodes is achieved. C, Li 2 S, and LiI are uniformly distributed on the lithium surface via a "saun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…The low LUMO of the additives causes their preferential reduction before electrolyte on the surface of lithium, forming SEI with excellent properties. [ 70 ] Common additives contain organic compounds (such as, vinylene carbonate, [ 71 ] trimethylsilyl azide (TSA), [ 63 ] 2‐(triphenylphosphoranylidene) succinic anhydride, [ 72 ] tris(pentafluorophenyl)borane, [ 70 ] fluoroethylene carbonate, [ 73 ] thiourea, [ 74 ] adiponitrile, [ 75 ] and polydimethylsiloxane [ 76 ] ), lithium salt (such as, LiPF 6, [ 77 ] LiPO 2 F 2 , [ 78 ] LiF, [ 51 ] and LiNO 3 [ 79 , 80 ] ), HF, [ 51 ] and gas molecules (such as, SO 2 [ 81 ] ). Among them, F‐rich, S‐rich, N‐rich chemicals have been extensively studied.…”
Section: Strategies To Solve Issues Of the Lithium Anodementioning
confidence: 99%
“…The low LUMO of the additives causes their preferential reduction before electrolyte on the surface of lithium, forming SEI with excellent properties. [ 70 ] Common additives contain organic compounds (such as, vinylene carbonate, [ 71 ] trimethylsilyl azide (TSA), [ 63 ] 2‐(triphenylphosphoranylidene) succinic anhydride, [ 72 ] tris(pentafluorophenyl)borane, [ 70 ] fluoroethylene carbonate, [ 73 ] thiourea, [ 74 ] adiponitrile, [ 75 ] and polydimethylsiloxane [ 76 ] ), lithium salt (such as, LiPF 6, [ 77 ] LiPO 2 F 2 , [ 78 ] LiF, [ 51 ] and LiNO 3 [ 79 , 80 ] ), HF, [ 51 ] and gas molecules (such as, SO 2 [ 81 ] ). Among them, F‐rich, S‐rich, N‐rich chemicals have been extensively studied.…”
Section: Strategies To Solve Issues Of the Lithium Anodementioning
confidence: 99%
“…It has been shown that a layer of Li 2 S, when formed with a gas-solid reaction and used in a polysulfide-free system, can be used to realize a stable lithium-metal anode. [72][73][74] In order to investigate the role played by polysulfide species in modulating the characteristics of lithium deposition, the deposited lithium in anode-free Ni || Li 2 S full cells and equivalent Ni || Li half cells was characterized with ToF-SIMS. The electrolyte employed was E1, which is 1 m LiTFSI + 0.1 m LiNO 3 .…”
Section: Role Of Polysulfides In Stabilizing Lithium Deposition In LImentioning
confidence: 99%
“…Nan et al proposed a totally different approach for the formation of an inorganic SH aSEI. [189] The artificial layer was produced through an in situ gas-solid "sauna" reaction between CS 2 -I 2 steam and Li metal. The so obtained composite SEI was constituted by a porous carbon scaffold embedding lithium ion conductive species as LiI and Li 2 S. The key feature is the mobility of LiI from the liquid electrolyte toward the electrode that can reform the layer after breakage, protecting the newly exposed lithium surface and bypassing the appearance of preferential nucleation sites.…”
Section: Self-healing Artificial Solid-electrolyte Interfacesmentioning
confidence: 99%